Direct observation of phonon emission from hot electrons: spectral features in diamond secondary electron emission - O'Donnell, Kane; Edmonds, M.; Ristein, J.; Rietwyk, K.; Tadich, A.; Thomsen, L.; Pakes, C.; Ley, L. (Institute of Physics Publishing Ltd., 2014)
In this work we use high-resolution synchrotron-based photoelectron spectroscopy toinvestigate the low kinetic energy electron emission from two negative electron affinity surfacesof diamond, namely hydrogenated and lithiated diamond. For hydrogen-terminated diamondelectron emission below the conduction band minimum (CBM) is clearly observed as a resultof phonon emission subsequent to carrier thermalization at the CBM. In the case of lithiateddiamond, we find the normal conduction band minimum emission peak is asymmetricallybroadened to higher kinetic energies and argue the broadening is a result of ballistic emissionfrom carriers thermalized to the CBM in the bulk well before the onset of band-bending.In both cases the spectra display intensity modulations that are the signature of optical phononemission as the main mechanism for carrier relaxation. To our knowledge, these measurementsrepresent the first direct observation of hot carrier energy loss via photoemission.